Optimal preview control design of pneumatic servo system: a comparative analysis. (12th November 2019) - Kaur, Randeep; Ohri, Jyoti
This paper describes the development of a preview controller based on optimal control theory for positioning control of a pneumatic servo system. The preview theory of tracking control using the future information has been studied extensively but did not get enough applications in the field of servo control systems, used in modern industrial processing, that will increase the accuracy and efficiency of the industrial product. In the pneumatic servo system, the position of pneumatic cylinder is the command input and its future information can be known a priori. The proposed control system is composed of feedback from the state of the plant and feed-forward from the reference signal by using future information. The validity of the proposed control system is confirmed by simulation results and comparative analysis is done with standard optimal control. Simulation results imply that good performance and good phase characteristics can be obtained using optimal preview controller.